The Effect of Tax Socialization and the Implementation of E-Samsat on the Compliance of Motor Vehicle Taxpayers with Tax Sanctions as a Moderation Variable (Case Study on Sumedang Samsat Office Taxpayers) - Krisdina, Tiana Fenny; Salsah, Silma Halimatis; Azizah, Winny Salma Nur; Syiafudin, Ahmad (Journal of Business, Accounting and Finance, 2025)
This study aims to test the hypothesis and produce empirical evidence regarding the effect of tax socialization and the application of e-samsat on the compliance of motor vehicle taxpayers with tax sanctions as a moderation variable. This study uses a quantitative approach with a sample of 100 respondents with a sampling technique, namely Simple Random Sampling. The data was analyzed using multiple linear regression analysis methods and Moderate Regression Analysis (MRA) with the help of the SPSS 29 program. The results of the study showed that the variable of tax socialization had no significant effect on taxpayer compliance (0,091>0,05). Implementation of e-samsat had a significant positive effect on taxpayer compliancae (0,001<0,05). Based on the Moderated Regression Analysis (MRA) test, the tax socialization interaction moderated by tax sanctions has a significant value of 0,504>0,05, so it is stated that tax sanctions are not able to strengthen tax socialization on taxpayer compliance. Implementation of e-samsat moderated by tax sanctions has a signifcant value of 0,391>0,05 so that it is stated that tax sanctions are not able to strengthen the relationship between the implementation of e-samsat and taxpayer compliance